Strategic Flexibility Mediating the Impact of Entrepreneurial Orientation on Organizational Excellence - AlHalaseh, Rula Hani; Ayoub, Ziad (International Review of Management and Marketing, 2021)
The study aimed to analyze the impact of entrepreneurial orientation in achieving organizational excellence through strategic flexibility. This research is a quantitative study. The population of this study consists of all managers in the upper and middle management at the Jordanian Commercial Banks. The study conducted a comprehensive survey, by using its population as a sample, which totals 1023 managers. The data collection tool is a questionnaire that consists of 29 items was developed. The results show that the level of availability of entrepreneurial orientation, organizational excellence, and strategic flexibility has reached a high degree at Jordanian Commercial Banks. Other findings show that entrepreneurial orientation in its combined dimensions (innovative entrepreneurial orientation, proactive entrepreneurial orientation, and risk-taking entrepreneurial orientation) has a statistically significant impact on achieving organizational excellence through strategic flexibility in Jordanian commercial banks. From the findings, the authors conclude that strategic flexibility plays a partial mediating role between entrepreneurial orientation (with all its dimensions) and organizational excellence. At the same time, strategic flexibility fails to play a mediator role between entrepreneurial orientation dimensions and organizational excellence. Keywords: Entrepreneurial Orientation, Organizational Excellence, Strategic Flexibility, Commercial Banks, Jordan. JEL Classifications: L1, L2, M1 DOI: https://doi.org/10.32479/irmm.12520